A mixed methods approach to understanding cyberbullying: A role for both quantitative and qualitative research. - MC GUCKIN, CONOR; Espey, K; Duffy, J (My University, 2013)
The study investigated the incidence and nature of cyber-bullying within six post-primary schools in Northern Ireland. A mixed methods sequential explanatory design was employed. The first, quantitative phase involved questionnaires with 757 year 8 and year 11 pupils (57.5% females, n = 435; 42.5% males, n = 322) ranging in age from 11 to 15 years (mean = 13.04 years). The second, qualitative phase involved focus groups with two groups of pupils (n = 14). Cyber-bullying was less frequent than traditional bullying but levels were concerning. Bullying via the use of videos on a mobile phone was perceived to be most harmful. Pupils suggested blocking messages / numbers as the best coping strategy and many cyber-victims did not tell anyone about their experiences. Discussions with the young people suggested that the generational gap in understanding and knowledge of communication media may be one reason why young people are not choosing to tell adults. Cyber-bullying is a complex and concerning form of bullying. The study illustrated the value of person centred approaches, together with quantitative methods, as a design for investigating bullying behaviour. Implications for future research and interventions are discussed.
PUBLISHED
Keywords: Cyberbullying